Leveraging Artificial Intelligence to Personalize Teacher Training Programmes: An Empirical Investigation of Teachers’ Perception and Readiness in Three Colleges of Education in Nigeria - Terzungwe, Benjamin Iorhemen; Idadu, John; Ayuba, Bala; Aliyu, Dahiru (Kashere Journal of Education, 2025)
The integration of artificial intelligence (AI) in teacher education presents significant opportunities for personalising professional training and enhancing pedagogical competence. This study investigates teachers’ perceptions and readiness to leverage AI for personalised teacher training at three colleges of education in Nigeria. Specifically, the objectives of this study were to: The study examines how teachers perceive and prepare for the use of AI in personalised training across three Colleges of Education in Nigeria. Specifically, the goals of this study were to: look at how teachers feel about using Artificial Intelligence in teacher training programs; find out how ready teachers are to use AI tools for personalised training; identify factors related to their schools and resources that affect teachers' readiness to use The study is based on the Unified Theory of Acceptance and Use of Technology (UTAUT), Human Capital Theory (HCT), and Inclusive Pedagogy Framework (IPF), and it uses a descriptive survey design with 360 lecturers chosen through a random sampling method. A validated questionnaire with a reliability coefficient of 0.87 was employed to collect quantitative data, which were analysed using descriptive and inferential statistics. Findings reveal that teachers have positive perceptions of AI's potential to individualise and enhance training efficiency, but their readiness levels are moderate due to inadequate infrastructure, limited digital competence, and policy gaps. Performance expectancy and facilitating conditions emerged as the most significant predictors of AI adoption. The study concludes that institutional support, sustained professional development, and inclusive digital policies are critical to building AI readiness in teacher education. It recommends curriculum integration of AI literacy, infrastructure improvement, and targeted capacity-building initiatives. The findings have implications for policy formulation, institutional planning, and the sustainable digital transformation of teacher training programs in Nigeria.